Optimalisasi Website Manajemen Unira Malang Sebagai Sarana Peningkatan Informasi dan Promosi - Nurul Ainun Hafidhoh; Nurul Aini Fariha; Ridho Ikwansyah; Adita Nafisa (Student Research Journal, 2025)
The development of internet-based information technology enables universities to improve the accessibility and quality of information for prospective students through websites. Websites serve as strategic platforms for information dissemination, promotion, and digital branding to reach a wider audience. This study aims to optimise the website of the Management Programme at Raden Rahmat Islamic University (Unira) Malang To enhance its efficiency in delivering the latest information to both current and prospective students. Using a qualitative method with a case study approach, this research collected data through literature review, observation, and documentation. Findings indicate that optimising the website facilitates prospective students’ access to the latest information and allows lecturers to upload student achievements. This website development strengthens the Management Programme's image at Unira Malang, improving its public reputation and increasing its visibility.